Temporal Characteristic of the Mesoscale Plasma Flow Perturbations in the High‐Latitude Ionosphere. Issue 1 (3rd January 2019) - Chen, Yun‐Ju; Heelis, Roderick A.
Abstract: Spatial and temporal characteristics of flow perturbations in the high‐latitude ionosphere are important considerations for energy deposition from the magnetosphere. In this study, we examine the temporal characteristics of plasma flow perturbations with spatial scales between 100 and 400 km from two consecutive Defense Meteorological Satellite Program (DMSP) passes that have about the same orbital plane and sample time spacing between a few seconds and 20 min during local summer seasons in 2007‐2015. The temporal characteristics of mesoscale flow perturbations are described by rise and saturation times for growth and decay derived from the changes in magnitude of perturbations and the time separation between consecutive samples. Observations suggest that the rise times for both growth and decay are shorter for small spatial scales (1–2 min, 100–200 km) and longer for large spatial scales (3–5 min, 200–400 km). The saturation time for decay is 10 min for small scales and 20 min for large scales. The growth saturation time is about 5–10 min for both scale sizes. These characteristic times for growth are always shorter than the decay times. If the difference in these characteristic times between growth and decay is produced by motion of a perturbation with the background flow through the observed volume, then a longitudinal scale size of 750 km or 1.5 hr of local time is implied. Key Points: Residence time is longer for larger scale size flow perturbations in a fixed volume The growth times for all scale size are shorter than decay times A weak dependency on geomagnetic activity is seen but no dependency on IMF B z